2012
DOI: 10.1371/journal.pone.0041321
|View full text |Cite
|
Sign up to set email alerts
|

Seropositivity of Lyme Borreliosis and Associated Risk Factors: A Population-Based Study in Children and Adolescents in Germany (KiGGS)

Abstract: BackgroundLyme borreliosis (LB) caused by spirochetes of the Borrelia burgdorferi sensu lato complex is the most common tick-borne disease in the northern hemisphere. Data on the distribution and on risk factors in Germany are sketchy.Methodology/Principal FindingsBlood samples of a nationwide population-based cross-sectional study from 2003–2006 in children and adolescents aged 1 to 17 years in Germany (KiGGS) were analysed (n = 12,614) to assess the seroprevalence of anti-Borrelia antibodies. Data from stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
40
6
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 33 publications
15
40
6
7
Order By: Relevance
“…Several different studies confirmed the association between the occurrence of antibodies and outdoor activities, e.g., gardening [23] or contact with animals, especially among the cat owners in the households of German children [1] and dog owners [21]. Such a ativities as gardening and hunting appeared as insignificant risk factors in this study (P>0.05).…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Several different studies confirmed the association between the occurrence of antibodies and outdoor activities, e.g., gardening [23] or contact with animals, especially among the cat owners in the households of German children [1] and dog owners [21]. Such a ativities as gardening and hunting appeared as insignificant risk factors in this study (P>0.05).…”
Section: Discussionsupporting
confidence: 82%
“…burgdorferi antibodies (P= 0.045). Generally, it was confirmed that men work more frequently in the outdoor environment than women [1,3,8,11].…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations